BOOK REVIEWS (Journal of Finance, 1964)
Book reviewed in this article: Business Finance: Analysis for Financial Decisions . By W illiam B eranek . Financial Institutions, Their Role in the American Economy . By G ilbert W. C ooke , C harles L. P rather , F rederick E. C ase, and D ouglas H. B ellemore . Competition in the Synthetic Rubber Industry . By C harles F. P hillips , J r . Investment Decisions in Small Business . By M artin B. S olomon , J r . A Critical Study of Accounting For Business Combinations . By A rthur R. W yatt . Consumer Finance: The Poor Pay More . By D avid C aplovitz . 1962 Survey of Consumer Finances . By G eorge K atona , C harles A. L ininger and R ichard F. K osobud . Personal Finance . By E. B ryant P hillips and S ylvia L ane . International Finance: Reserve‐Asset Preferences of Central Banks and Stability of the Gold‐Exchange Standard . By P eter B. K enen . Non‐Merchandise Transactions Between Canada and the United States . By J ohn W. P opkin . The International Economy . By J ohn P. Y oung . Investments: A History of Interest Rates . By S idney H omer . SEC Accounting Practice and Procedure . By Louis R appaport , C.P.A. 2nd edition. Money and Banking: The Federal Reserve and the Treasury . By B oard of G overnors of the F ederal R eserve S ystem and the U nited S tates T reasury D epartment . Money, Prices, and Policy . By W alter W. H aines . Monetary Policy and the Financial System . By P aul M. H orvitz . Money and Banking—Analysis and Policy . By C harles R. W hittlesey , A rthur M. F reedman, and E dward S. H erman . Monetary Control . By E lmer W ood . Toward a Monetary Constitution . Edited by L eland B. Y eager . Public Finance: Tax Policy on United States Investment in Latin America . A Symposium. Tax Institute of America. National Income—Its Measurement, Determination, and Relation to Public Policy . By S am R osen . Public Finance and Budgetary Policy . By A lan W illiams . Real Estate Finance: Investment Time Scheduling in Urban Reconstruction . By L eland S. B urns . Real Estate Appraisal and Investment . By S anders A. K ahn , F rederick E. C ase and A lfred S chimmel .